Electroacupuncture pretreatment ameliorates anesthesia and surgery-induced cognitive dysfunction in aged rats: insights from gut microbiota modulation - Lei, Huajuan; Li, Ziou; Deng, Juan; Lei, Heng; Li, Honghui; Ding, Zhendong (Frontiers in Microbiology, 2025)
ObjectiveThis study aimed to investigate the effects of electroacupuncture (EA) on postoperative cognitive dysfunction (POCD) and gut microbiota in aged rats anesthetized with propofol.MethodsForty 18-months-old male SD rats were randomly divided into four groups: Sham, Model (MD), Sham Electroacupuncture (JE), and Electroacupuncture (EA), with 10 rats in each group. The Sham group underwent a skin incision without surgery, while the MD, JE, and EA groups received propofol anesthesia followed by right tibial surgery. The EA group received electroacupuncture at Baihui, Shenmen, and bilateral Zusanli points for 5 days prior to surgery, while the JE group received acupuncture without electrical stimulation. Behavioral tests, including the Morris water maze and open field tests, were conducted at 1-, 2-, and 3-weeks post-surgery to assess cognitive function. Gut microbiota composition was analyzed using second-generation sequencing.ResultsAt 1-week post-surgery, the MD, JE, and EA groups showed longer latencies and fewer crossings in the behavioral tests. However, at 3- and 4-weeks post-surgery, the EA group exhibited significantly reduced latency and increased crossing times compared to the MD and JE groups. Gut microbiome analysis revealed that the EA group had a higher relative abundance of Bacteroidetes and Proteobacteria, and a reduced relative abundance of Unclassified Lactobacillaceae compared to the MD and JE groups.ConclusionElectroacupuncture was associated with improved postoperative cognitive function in aged rats after propofol anesthesia and tibial surgery. These effects were accompanied by alterations in gut microbiota composition, suggesting a possible link with the gut–brain axis, although causality remains to be established.